Aerosol Assisted Synthesis of Y/ZSM‐5 Composite Zeolite and Its Application in Cracking Reaction. Issue 24 (8th August 2022) - Xiong, Guang; Zhou, Shengyang; Liu, Liping; Qian, Ji; Liu, Jiaxu; Zhao, Leping
Abstract: Y/ZSM‐5 composite zeolite was synthesized by an aerosol assisted hydrothermal method including a two‐step crystallization. The aerosol technique was used to prepare the precursor of Y/ZSM‐5 composite zeolite. This helped to fully utilize the amorphous silica‐alumina species left in the primary crystallization solution of NaY zeolite, and to bring the two zeolites close to each other during the second crystallization step. The optimal adding sequence and synthesis conditions were investigated to reduce the amount of template and accelerate the crystallization rate. The composite zeolites were analyzed using XRD, SEM, nitrogen physical adsorption, NH3 ‐TPD techniques. It was found that the acid properties can be adjusted by modulating the SiO2 /Al2 O3 molar ratio of the secondary crystallization feed. The BET specific surface area of the optimal Y/ZSM‐5(20) composite zeolite is 502 m 2 /g, the pyrolysis conversion rate of 1, 3, 5‐triisopropylbenzene reaches 95.1 %, and the selectivity to benzene reaches 53.4 %. Abstract : Y/ZSM‐5 composite zeolite was synthesized by an aerosol‐assisted hydrothermal method including a two‐step crystallization. The structure and acidity of the composite zeolite can be modulated by monitoring the synthesis conditions.